Lung Transplantation for Pleuroparenchymal Fibroelastosis: A Single-Center Experience with Revision of Literature - Eleonora Faccioli; Vincenzo Verzeletti; Chiara Giraudo; Marco Schiavon; Fiorella Calabrese; Monica Loy; Federico Rea; Andrea Dell’Amore (Biomedicines, 2023)
Pleuroparenchymal fibroelastosis (PPFE) is a rare condition characterized by fibrosis involving the pleura and the upper lobes which can be idiopathic or secondary to chemotherapy, transplantations and occupational exposure. For the end-stage form, lung transplantation (LT) is the treatment of choice. The aim of this study was to report our single-center experience for patients subjected to LT for PPFE and comparing it with the already published evidence on this topic. At our center, we have performed 6 bilateral LTs for patients with PPFE (3 males and 3 females) with a median age of 52 years. Median ICU and in-hospital length of stay were 8 and 30 days, respectively. To date, two patients are alive and four are dead, with a median overall survival of 10 months. In addition, after a formal search using the terms “pleuroparenchymal fibroelastosis AND lung transplantation”, we collected 14 studies focused on outcomes after LT. LT for PPFE is technically challenging and its post-operative course could also be complicated. Current available data on LT outcomes are extremely poor and mostly limited to case reports. Further studies need to be published to improve knowledge of this disease and to achieve best outcomes for LT.